Toward a Proposed Ontology for Nanoscience - Tanaka, Michiko (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
As is typical for other emerging fields of science, there are no readily available databases or detailed classification schemes for nanoscience. I propose analyzing the controlled index terms and classifications used in articles in the premier nanoscience journals indexed in INSPEC, and generate a meta-level ontology for nanoscience. Comme il est typique dans certains domaines émergents de la science, il n’existe aucune base de données déjà disponible ou de schémas de classification pour la nanoscience. Je propose d’analyser les termes d’indexation contrôlés et les classifications utilisées dans les articles des premiers journaux traitant de nanoscience indexés dans INSPEC et de créer une ontologie de méta niveau pour la nanoscience.